Olivia - Paramount Home Entertainment (Firm); Nickelodeon (Television network) (Hollywood, Calif. : Paramount Home Entertainment, 2009)
Olivia is a feisty pig who has too much energy for her own good. No matter what she is doing, she never gets worn out. Of course, her loving parents aren't quite so energetic.
Olivia acts out -- Olivia and grandma's visit -- Olivia and the crystal ball -- Olivia plays soccer -- Olivia plays piano -- Olivia trains her cat -- Olivia packs up -- Olivia is invited to dinner.
Full screen.
Originally produced for the television program Olivia.
Animated.
Special features: Olivia photo gallery.
Not rated.
DVD; Dolby Digital stereo., NTSC.
Keywords: Olivia (Fictitious character : Falconer) -- Juvenile films; Swine -- Juvenile films; Imagination -- Juvenile films; Television programs for the hearing impaired; Television programs; Animated television programs; Children's television programs